Morphology and phylogenetic analyses reveal Montagnula puerensis sp. nov. (Didymosphaeriaceae, Pleosporales) from southwest China - Du, Tianye; Hyde, Kevin D.; Mapook, Ausana; Mortimer, Peter E.; Xu, Jianchu; Karunarathna, Samantha C.; Tibpromma, Saowaluck (Phytotaxa, 2021)
A dead woody sample of Acer sp. with fungal fruiting bodies was collected in Pu’er City of Yunnan Province. Multigene phylogenetic analyses of LSU, ITS, SSU, and tef1-α sequence data showed that our collection belongs to Montagnula and is well separated from all other extant species. Montagnula puerensis is compared with all extant species by morphological characteristics, culture characteristics, host, and location information and is the first report of Montagnula from the host genus Acer.